Sulphur-rich functionalized calix[4]arenes for selective complexation of Hg2+ over Cu2+, Zn2+ and Cd2+. Issue 38 (2nd September 2016) - Bensenane, Bachir; Asfari, Zouhair; Platas-Iglesias, Carlos; Esteban-Gómez, David; Djafri, Fatiha; Elhabiri, Mourad; Charbonnière, Loïc J.
Abstract : ON–OFF fluorescent chemosensors based on sulphur-rich functionalized calix[4]arenes selectively bind Hg 2+ over Cu 2+, Zn 2+ and Cd 2+ . Abstract : The syntheses of two new ligands based on a calix[4]arene scaffold in the cone conformation functionalized on the phenolic positions 1 and 3 by diethylthiophosphonates (L1 ) or tetra(tri)thioethyleneglycol (L2 ) crowns are described. Together with ligandL3, the parent calix[4]arene substituted by a penta(tetra)thioethyleneglycol crown, the spectroscopic properties of the ligands were determined by means of UV-Vis absorption spectroscopy and steady-state and time-resolved fluorescence spectroscopy, showing that the ligands display modest but non-negligible intrinsic fluorescence properties ( ϕ fluo = 0.023; 0.026 and 0.029 forL1, L2 andL3 in CH2 Cl2, respectively). The X-ray crystal structures of ligandL1, and of its synthetic precursor were determined and analyzed for their capacity to accommodate the incoming cationic species. The ligands were further investigated for their complexation properties of divalent cations such as Cu 2+, Zn 2+, Hg 2+ and Cd 2+ (under their nitrate salts) in 1 : 1 CH3 CN/CH2 Cl2 solutions ( I = 0.01 M Et4 NNO3, T = 25.0(2) °C), in which the additions of cations were monitored by absorption and steady-state fluorescence spectrophotometries. The stoichiometries of the corresponding complexes were assessed by ESI-MS, while insights into the structures of the complexes in solution were obtained with density functional theory (DFT) calculations. The influence of the sulphur and phenol coordinating moieties was addressed to show that the thiocrown compoundsL2 andL3 displayed a marked affinity towards the soft mercuric cation (Δlog  K ≥ 2), with no particular size selectivity effect, whereas ligandL1 can accommodate both the thio and phenol units to coordinate with Cu(ii ). Altogether, these results point to the use ofL3 as a selective fluoroionophore for detection of Hg 2+ .